1997
DOI: 10.1152/jappl.1997.83.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of treadmill running on femoral bone in young orchidectomized rats

Abstract: Forty 6-wk-old male Wistar rats weighing 308 +/- 24 g were divided into two groups. On day 0, the 20 animals in one group were surgically castrated and the other group was sham operated. Within each group, 10 rats were selected for treadmill running (60% maximal O2 consumption, 1 h/day, 6 days/wk for 15 wk). The 20 sedentary rats were used as controls. At the time the rats were killed (day 105), running had no significant effect on femoral mechanical properties either in castrated or in sham-operated rats. Fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
1
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 39 publications
6
22
1
2
Order By: Relevance
“…[74] Experiments with rats have shown that running has osteogenic effects on loaded bones of young male [75] and female [76,77] rats, as well as in ovariectomized [78] and orchidectomized rats, [79] although the osteogenic effect of exercise appears to be less efficient in female ovariectomized rats. [78] The forces generated during running play a role in the osteogenic response, since the rats that run with a loaded backpack on top of their back show a greater gain in bone mass than the rats running without extra load.…”
Section: Experiments With Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[74] Experiments with rats have shown that running has osteogenic effects on loaded bones of young male [75] and female [76,77] rats, as well as in ovariectomized [78] and orchidectomized rats, [79] although the osteogenic effect of exercise appears to be less efficient in female ovariectomized rats. [78] The forces generated during running play a role in the osteogenic response, since the rats that run with a loaded backpack on top of their back show a greater gain in bone mass than the rats running without extra load.…”
Section: Experiments With Animalsmentioning
confidence: 99%
“…11 wk HPC-tibia, L2, T2 volume trabeculae Horcajada et al [79] (1997) [76] (1993) ER = 28 DR = 24 C = 30 F 6 5 /wk 20 m/min 6 wk Denervated rats HPC-tibia cortical bone area in ER vs DR, C Van der Wiel et al [80] (1995) ER1 = 10 ER2 = 10 ER3 = 10 C = 14 DXA-WB, LL 16% LL BMD ER1 vs C 15% LL BMD ER2 vs C 15% WB, 20% LL BMD ER3 vs C BMD = bone mineral density; C = controls; CXE = castrated exercising rats; DR = sciatic denervated rats; DXA = dual x-ray absorptiometry; ER = exercising rats; HPC = histomorphometric analysis; L2 = second lumbar vertebra; L4 = fourth lumbar vertebra; LL = lower limbs; M/F = male/female; n = number of subjects; OXE = ovariectomized exercising rats; OXS = ovariectomized sedentary rats; QTC = quantitative CT; SHE = sham-operated exercising rats; T2 = second thoracic vertebra;…”
Section: Young Menmentioning
confidence: 99%
“…In contrast, the positive effect of physical exercise on bone metabolism shown by previous studies can be also explained by a mechanical impact of exercise on bone metabolism, because in these studies bone metabolism has been assessed in long bones, which are exposed to mechanical loading. [15][16][17][18][19][20] By using a cranial bone healing model, we can exclude that the local mechanical environment is responsible for the influence of physical exercise on vascularization during bone repair. Vice versa, we can Pearson's product-moment coefficient was used to determine the strength of association between the pairs of IVM parameters and running distances.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been demonstrated that physical exercise is capable of stimulating osteoblast proliferation, increasing bone mineral density and bone strength, and inhibiting bone resorption in osteoporotic and nonosteoporotic bone. [15][16][17][18][19][20] When using animal models, the transfer of results to the clinical situation should always be considered. Regarding the cranial window model, differences in the anatomy, morphology, blood supply, and healing process of membranous bones like the calvarium and long bones have to be addressed.…”
Section: Exercise and Angiogenesis During Bone Repairmentioning
confidence: 99%
See 1 more Smart Citation